Circulating chromogranin B levels in patients with acute respiratory failure: data from the FINNALI Study. (17th November 2017) - Myhre, Peder Langeland; Stridsberg, Mats; Linko, Rita; Okkonen, Marjatta; Nygård, Ståle; Christensen, Geir; Pettilä, Ville; Omland, Torbjørn; Røsjø, Helge
Abstract: Purpose: Circulating chromogranin B (CgB) levels are increased in situations characterized by systemic and myocardial stress, but whether CgB provides prognostic information in patients with acute respiratory failure (ARF) is unknown. Methods: We included 584 patients with ARF, defined as ventilatory support >6 h, and with blood samples available on Intensive Care Unit (ICU) admission and day 3 ( n = 479). CgB levels were measured by radioimmunoassay and follow-up was 90 days. Results: One-hundred-sixty-nine patients (29%) died during follow-up. Admission CgB levels separated non-survivors from survivors: median 1234 (Q1-3 989–1742) vs. 917 (753–1224) pmol/L, respectively, p < 0.001. CgB levels on ICU admission (logarithmically transformed) were associated with time to death after adjustment for established risk indices available on ICU admission, including N-terminal pro-B-type natriuretic levels: HR 2.62 (95%C.I. 1.82–3.77), p < 0.001. Admission CgB levels also improved prognostication on top of SOFA and SAPS II scores as assessed by Cox regression analyses and the category-free net reclassification index. The area under the curve (AUC) for admission CgB levels to separate survivors and non-survivors was 0.72 (95%CI 0.67–0.76), while the AUC on day 3 was 0.60 (0.54–0.66). Conclusions: CgB levels measured on ICU admission provided additional prognostic information to established risk indices in ARF patients.